2013
DOI: 10.2298/bah1301145b
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between protein to fat ratio of milk and chemical parameters and the yield of semi-hard cheese

Abstract: In order to obtain good cheese quality, the milk has to possess good physical-chemical properties and should originate from healthy cows. Since milk fat and milk protein are the main constituents of cheese, their proportion in milk is of particular importance for the product yield and quality. This paper describes studies on the protein to fat ratio of milk and the consequent influence on the chemical composition and yield of semi-hard cheese, commercially called "Montenegrin naturally dried cheese". The tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The findings of the present study can be co-related to a higher TS content in goat milk cheese for the treated group. These findings agree with the findings of Rasovic et al (2013) and Karki and Ojha (2018). On the contrary, Waheed et al ( 2017) reported higher moisture content ranging between 49.45±0.12 to 51.52±0.16 using plant coagulant and between 61.00 to 62.90% using different forms of iron (Khalifa, 1996), while Indumathi et al (2013) reported low moisture content in iron-fortified Gouda cheese samples which might probably be due to different processing techniques used in the preparation of mozzarella and gouda cheeses.…”
Section: Moisturesupporting
confidence: 93%
“…The findings of the present study can be co-related to a higher TS content in goat milk cheese for the treated group. These findings agree with the findings of Rasovic et al (2013) and Karki and Ojha (2018). On the contrary, Waheed et al ( 2017) reported higher moisture content ranging between 49.45±0.12 to 51.52±0.16 using plant coagulant and between 61.00 to 62.90% using different forms of iron (Khalifa, 1996), while Indumathi et al (2013) reported low moisture content in iron-fortified Gouda cheese samples which might probably be due to different processing techniques used in the preparation of mozzarella and gouda cheeses.…”
Section: Moisturesupporting
confidence: 93%
“…2007; Bojanić‐Rašović et al . 2013). Milk composition can be altered at the production stage, through genetic and nutritional manipulation, or postproduction by processors through technological means (Rattray and Jelen 1996)—the latter of which is the focus of this report section.…”
Section: Milk Standardisation Protocols For Cheese Manufacturing As A...mentioning
confidence: 99%
“…When the composition and quality of milk fluctuate over the cheesemaking season, it can be challenging to maintain consistency in both cheese composition and quality, especially when cheese production standard operating procedures (SOPs) are not created to consider these variations. To this end, studies conducted to mimic the effects of seasonal variations in milk composition have shown that lactose concentration, protein-to-fat ratio, and milk fat and protein concentrations all significantly affect the composition and quality of cheese (Verdier-Metz et al 2001;Guinee et al 2007;Bojanić-Rašović et al 2013). Milk composition can be altered at the production stage, through genetic and nutritional manipulation, or postproduction by processors through technological means (Rattray and Jelen 1996)-the latter of which is the focus of this report section.…”
Section: Milk Standardisation Protocols For Cheese Manufacturing As A...mentioning
confidence: 99%
“…The reduction in milk fat content with respect to protein affects the physical and chemical properties of cheese as well as the fat content in cheese itself, since it is responsible for the amount of milk fat that remains in the curd. Under the same production conditions and the same technological procedure, cheeses from milk with higher fat content have a finer, softer consistency, while the cheeses obtained from milk with lower fat content have a tough consistency [19].…”
Section: Fat and Protein Content And Reverse Syndromementioning
confidence: 99%